(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Physical activity plays a vital role in supporting the physical health, mental well-being, and cognitive function of university students. Several studies have demonstrated that physical activity positively contributes to executive brain function, working memory, and concentration. These cognitive functions are directly related to students’ academic performance. Despite this, physical activity levels among university students tend to be low, especially in higher education environments dominated by sedentary behavior. In this context, a community-based approach is viewed as a potential strategy for sustainably increasing student participation in physical activity. This narrative review aims to explore the role of community-based approaches in facilitating active lifestyles among university students and to identify their implications for university policy development. Through an analysis of recent literature, social engagement and environmental support have been identified as key factors that make this approach relevant and applicable to campus settings. These findings provide a conceptual foundation for universities to consider community-based interventions as part of their strategic efforts to foster a campus culture that supports healthy lifestyles and optimal academic performance.